Makanah al-Masih fi al-Katsulikiyah 'inda al-Ghinustiyah - Akbar Aisya Billah (Journal of Comparative Study of Religions (JCSR), 2021)
This study aims to show the attitudes and views of Gnosticism towards the position of Jesus in the Catholic Church. The researcher uses the descriptive method to explain the meaning of Gnosticism, history, and also the characters of Gnosticism. In addition, the researcher also uses a critical analysis method that explains the attitude of Gnosticism to the position of Jesus in Catholicism. The results of the study found that Gnosticism has a concept of a different understanding of the figure of Jesus, and rejects the understanding of Jesus in Catholicism. Gnosticism does not recognize Jesus as a savior, because man's salvation will be obtained from man's own efforts and knowledge of God (Shopia). While Jesus was merely a spiritual teacher who brought the knowledge of God, and Jesus' resurrection was a delusion, Jesus did not rise physically but only spiritually.